Islamic Identity and Political Discourse in Hamka’s Tafsir Al-Azhar - Zhalifunnas, Gamal Akhdan; Fajar Islami Human (Journal of Ushuluddin and Islamic Thought, 2023)
The issue of identity politics frequently causes controversy and societal conflict, which often results in polarization and social fragmentation. This study seeks to analyze Hamka’s perspective on identity politics through a close examination of his Qur’anic exegesis, with particular attention to the ideological construction embedded in his interpretation. The primary source of analysis is Tafsir al-Azhar, a work written by Hamka’s role not only as a religious scholar but also as a prominent social and political activist whose interpretive approach is marked by strong political undertones. The study focuses on Hamka’s interpretation of key Qur’anic passages related to identity politics, specifically Surah al-Rūm [30]: 1–7, Surah al-Baqarah [2]: 142–143, and Surah al-Mā’idah [5]: 51. By using critical discourse analysis and historical-literary framework, the research reveals that Hamka emphasizes the necessity of identity politics as a means of affirming Islamic solidarity and loyalty. His interpretation reflects the political climate of his time, particularly his resistance to government policies which links to the Indonesian Communist Party (PKI), and is significantly shaped by the context of his imprisonment during the New Order regime.